2012
DOI: 10.1021/tx300160z
|View full text |Cite
|
Sign up to set email alerts
|

Does Carbon Black Disaggregate in Lung Fluid? A Critical Assessment

Abstract: Carbon black is an industrially produced particulate form of nearly pure elemental carbon. The basic building blocks of carbon black are (1) primary particles, minute pieces of matter with defined physical boundaries; (2) aggregates, collections of strongly bound or fused particles; and (3) agglomerates, collections of weakly bound aggregates. Industrial carbon black is produced within a closed reactor where the primary particles form aggregates, which become the indivisible entities of carbon black. These agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…A contentious issue is the potential deagglomeration of NMs. One side argues that currently there is no evidence and that it is unlikely with respect to the underlying knowledge of physical behavior that NMs deagglomerate in biological milieus (Creutzenberg et al 2012a; Levy et al 2012; Preining 1998). The other side counters that deagglomeration in the lung may occur for some, but not necessarily for all NMs (Mercer et al 2013; Oberdörster et al 1992a), keeping in mind the many possible, yet untested, NMs.…”
Section: Introductionmentioning
confidence: 99%
“…A contentious issue is the potential deagglomeration of NMs. One side argues that currently there is no evidence and that it is unlikely with respect to the underlying knowledge of physical behavior that NMs deagglomerate in biological milieus (Creutzenberg et al 2012a; Levy et al 2012; Preining 1998). The other side counters that deagglomeration in the lung may occur for some, but not necessarily for all NMs (Mercer et al 2013; Oberdörster et al 1992a), keeping in mind the many possible, yet untested, NMs.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon black particles with diameters less than 100 nm are referred to as ultrafine powder or carbon black nanoparticles (CBNPs) and are used as reference material for diesel exhaust particles stripped of their adsorbed compounds in toxicological studies (Levy et al, 2012;Kyjovska et al, 2015b). CBNPs are one of the most widely produced and used nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that annual carbon black (CB) emissions in China were 1957 Gg in 2007 and increasing in recent years [3]. NCBs are massively manufactured and widely used in industry, for purposes such as colorant of inks, coatings and plastic goods, UV shielding agent of plastic goods and as a reinforcing agent and filler of rubber accounting for 94% of the total carbon black production [4]. In recent years, researchers have carried out a series of in vivo and in vitro biocompatibility investigations of NCBs.…”
Section: Introductionmentioning
confidence: 99%